Potential of UNISKA's Integrated Laboratory Forage Land To Fulfilling Carrying Capacity In Dry Season (UNIVERSITAS ISLAM LAMONGAN, 2024)
The research aims to determine the potential of UNISKA's Integrated Laboratory forage land in fulfilling carrying capacity in dry season. This research was carried out in September - October 2023. This research used case study methods, measurements and direct observations in the field. Carrying capacity is measured using a comparison method between livestock feeding units and livestock units for livestock. The research results showed that UNISKA's Integrated Laboratory forage land has land area of 0,6433 ha. Dry matter of grass production is 1729,403 kg/0,6433ha, while dry matter of legumes is 120,286 kg/0,6433ha. The conclusion is carrying capacity of UNISKA's Integrated Laboratory forage land in dry season is 7,878 AU/ha.